NILAI EKONOMI TUMBUHAN (KAJIAN ETNOMEDISIN) OLEH MASYARAKAT ADAT MANDAR DI KECAMATAN LUYO, KABUPATEN POLEWALI MANDAR - Syamsuri Syamsuri; Hafsah Hafsah; Hasria Alang (Bio-Lectura : Jurnal Pendidikan Biologi, 2023)
One of the economic values of plants is that they can be used as medicine. Indonesian people since ancient times have used plants as traditional medicine. This knowledge has been passed down from generation to generation and there are differences between regions. This is due to differences in customs and experiences of people who use traditional medicine. Based on this, it is necessary to carry out an inventory or record of plants that act as medicines so that they can be properly documented. The purpose of this study was to obtain data on the types of plants used as traditional medicine by the local community. This research was conducted in West Pussui Village, Luwo District, Kab. Polewali Mandar, West Sulawesi. The method used is explorative which is descriptive qualitative in nature. The data collection technique used Participatory Rural Appraisal (PRA), through in-depth interviews covering the types of plants that can be used as medicine, their uses and how to mix the plants used. In addition to interviews, direct observation was also carried out to see the conditions at the research location. The technique of selecting respondents was done by snowball sampling. Data from interviews and observations were then presented in the form of pictures and tables and then analyzed using descriptive qualitative. The results showed that the people of the Mandar tribe used kirinyuh, guava, soursop, jatropha banana, cocoa duck, papaya, black turmeric, moringa, coconut, secang wood, bitter melon, meniran, lime, purslane and breadfruit as traditional medicine to treat various kinds of diseases. The part of the plant that is most widely used to treat diseases is the leaf with a percentage of 50%.